Aplikasi Konsep 'Ulama dan Intelektual: Satu Penilaian Kritis - Ahmad, Shukri (Jurnal Usuluddin, 2000)
This article attempt to examine the concept of 'ulama' and its relationship to the concept of Muslim Intellectual. Some of the general philosophical and conceptual issues in the light of contemporary intellectual positions regarding the classical Islamic religious traditions will be highlighted. In this article, the writer mentions several basic points to support the view that all 'ulama' are intellectuals but Muslim Intellectual are not necessarily 'ulama'.